MARKETING MANAGEMENT OF EDUCATIONAL SERVICES AT THE AL FALAH SUKOHARJO FOUNDATION EDUCATIONAL INSTITUTION - Tri Yulianto; Imam Makruf; Indah Nurhidayati (Universitas Muhammadiyah Surakarta, 2024)
This study aims to find out: 1) how to manage the marketing of educational services in the Al Falah Foundation Educational Institution, 2) supporting and inhibiting factors in marketing management, and 3) solutions to overcome obstacles. This research uses a qualitative method. The research was conducted at the Al Falah Foundation. Data collection techniques with observation, interview, and documentation methods. The subject of the study was the head of the foundation, the foundation informant, committee members, and several teachers. The results of the study show that: 1) Marketing management of educational services at the Al Falah Baki Foundation, by implementing various marketing management planning steps. Planning the foundation's vision, mission, and objectives, analyzing external threats and opportunities, and using various promotional media are things that the Al Falah Foundation emphasizes. In addition, the focus is on analyzing the education market, determining the target market, and holding internal and external meetings to increase the Foundation's visibility. 2) Supporting factors include school trust, the availability of PPDB human resources (HR), operational costs, and a good image in the community. On the other hand, obstacle factors include outside schools that refuse to visit schools for PPDB socialization, limited time given for socialization, and lack of human resources. 3) every solution in overcoming obstacles by making a memorandum with the school/madrasah to be visited, making a mature PPDB plan, and limiting the PPDB team properly.